APLIKASI PEMOTONGAN PAJAK REKLAME BERBASIS WEB - Kiki Agustin; Hasanah Tisna Amijaya; Asep Ririh Riswaya (STMIK Mardira Indonesia, Bandung, 2020)
This study aims to assist the work of cutting the advertisement tax at UPT Local Tax Region 2 Margahayu can be better in time utilization and data accuracy. The author conducts research using descriptive analysis methods, with the data collection techniques used are making observations, and literature studies that have a close relationship with the subject matter. From the results of the research, the obstacles that were found were in the advertisement tax calculation still using Microsoft Excel, and data processing had not been processed optimally, even though it had used computers. So it is necessary to have an application that can help companies in calculating the advertisement tax so that it is not done several times, making taxpayer reports and advertisement tax reports. One of the tools that can support this is the use of adequate computers and human resources to form a good application. So the billboard tax deduction application was made, this application was created using the PHP programming language, APACHE as a web server, and MYSQL as a database processing. It is hoped that with this application, problems that may arise can be resolved properly. Keywords: Tax, advertisement tax, billboard tax deduction, Bapenda Kabupaten Bandung DOI : http://doi.org/10.5281/zenodo.4320207